Laporan Kasus : Ruptur kornea + katarak traumatik OD dengan General Anestesi - Sukma Nugroho; ari wahyuni (Medula, 2021)
Ocular trauma is one of the main causes of visual impairment. Ocular trauma can be divided into sharp trauma, blunt trauma, chemical trauma and thermal trauma. Ocular trauma can cause cataracts called traumatic cataracts, which can result from penetrating or blunt trauma to the eyeball. Prompt and appropriate treatment can improve visual acuity. In this case report, an 8-year-old female patient came to the ER Abdul Moeloek Hospital with complaints of blurred vision in the right eye accompanied by sudden red eyes. This complaint was felt due to the patient playing with the simcard opening tweezers and the tweezers fell into the patient's eye in a piercing position. patient. In addition, the patient complained of vision in the right eye that felt like seeing fog and was dazzled when he saw light. Then the right eye felt watery, sore and felt lumpy. On physical examination, ocular ophthalmology with cloudy cornea and visible tears, shallow anterior ocular camera, uneven cloudy lens. This patient was diagnosed as right ocular corneal rupture with traumatic cataract and cataract extraction was planned with some prior anesthetic considerations. Complete preoperative, intraoperative, and postoperative management will improve the success of the operation.